KONSEP PEMERINTAHAN ISLAM IMAM KHOMEINI - Hartati Hartati (Kalam: Jurnal Agama dan Sosial Humaniora, 2017)
Western democracy has ruined the eastern world, especially the Islamic world. For that Muslims should teach the Western people about the meaning of democracy. Khomeni is a the father of Iran's revolution of fundamentalism, it did not escape the thinking pattern influenced by mystics, philosophy and tasawuf based on the teachings of the Qur'an and Hadith. The concept of a Government that demanded the Muslims to plunge into the political scene to direct the life of the Islamic community in line with the laws of God, both in terms of relating to the Government and the community. Khomeini offered a new model of democracy which is based on the teachings of Islam with the mention "genuine democracy". Therefore the prerequirement to be a leader should be a Muslim. The will of the people should be in line with the will of God. And alignment of the will are guarded and kept with the supervisory mechanism of the al-faqih over Government concept of Imamate in Shi'a teachings.